How to win a cosmic war : God, globalization, and the end of the War on Terror - Aslan, Reza. (New York : Random House, 2009)
A cosmic war is a religious war, not between armies or nations, but between the forces of good and evil, a war in which God is believed to be directly engaged on behalf of one side against the other. The hijackers who attacked the United States on September 11, 2001, thought they were fighting a cosmic war. Scholar Reza Aslan maintains that by infusing the War on Terror with the same kind of religiously polarizing rhetoric, the United States is also fighting a cosmic war--a war that can't be won. This book is both an in-depth study of the ideology fueling militants throughout the Muslim world, and an exploration of religious violence in Judaism, Christianity, and Islam. Aslan argues that we must strip conflicts of their religious connotations and address the earthly grievances that always lie behind the cosmic impulse. How do you win a cosmic war? By refusing to fight in one.--From publisher description.
Pt. 1: The geography of identity. The borderless self ; A land twice promised -- Pt. 2: God is a man of war. Zeal for your house consumes me ; An army of believers ; The near and the far -- Pt. 3: The end of the war as we know it. Generation E ; The middle ground.
Includes bibliographical references (p. [211]-214) and index.
Keywords: Jihad; Islamic fundamentalism; War on Terrorism, 2001-2009.; Globalization